Inovasi Manajemen Edukasi Kesehatan Berbasis Teknologi Dalam Meningkatkan Literasi Kesehatan Siswa Di Era Society 5.0 - Dian Mawarni (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
The Society 5.0 era demands increased student health literacy as an essential competency. However, previous research has tended to focus only on the health education aspect and has not comprehensively examined the integration of technology-based health education management. Therefore, this study aims to analyze the effectiveness of technology-based health education management innovations and identify key factors influencing their successful implementation. This study used a mixed methods approach with a sequential explanatory design. Quantitative data were collected through a survey of 200 students, while qualitative data were obtained through in-depth interviews with 10 teachers and the principal. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were analyzed using a thematic approach to strengthen the interpretation of the results. The results indicate that technology-based health education management innovations have a significant impact on improving student health literacy. Furthermore, it was found that successful implementation is influenced by five main factors: school institutional support, availability of technological infrastructure, teacher training, student motivation, and parental involvement. The novelty of this research lies in the integration of managerial and technological approaches in health education, tested through a mixed methods approach. These findings confirm that successful health literacy improvement is determined not only by the use of technology, but also by organizational readiness and multi-stakeholder collaboration. The implications of this research provide theoretical contributions to the development of technology-based health education management models and practical recommendations for educational institutions facing the challenges of Society 5.0.